Tales of peasants, traders, and officials: contracting in rural Andhra Pradesh, 1980-82 - Bell, Clive (World Bank Group, 2020)
Tales of Peasants, Traders, and Officials: Contracting in Rural Andhra Pradesh, 1980-82 stems from a research project in the subfield of rural economic organization, with a focus on credit and irrigation, and on how public policy in these domains influenced agricultural development. The fieldwork was carried out in three states of the Indian Union between 1980 to 1982, including 14 villages in Andhra Pradesh. The survey covered villagers' dealings in the markets for labor, tenancies, credit, and crops. It revealed not only diverse contractual forms in those markets, but also their interplay with access to credit and its terms. Understanding what motivates agents to contract in a particular way-or not at all-is essential in such a study. At the beginning and toward the close of the survey work, the principal investigators conducted interviews with focus groups, some respondents in the household sample, and various public officials, who were encouraged to speak freely. The first part of the monograph comprises an introductory chapter and two long travelogues, which provide structured accounts of the proceedings of those interviews. Next are formal analyses of various alternative contractual arrangements and the villagers' choices among them. These are partly inductive; they draw on what respondents had to say about their options and decisions as well as received theory. Four topics are treated in detail: (1) the choice between employment as a casual laborer and as an attached farm servant; (2) the choice between sharecropping and fixed-rents paid in kind, with special reference to land irrigated by percolation wells; (3) the closely related matter of loans, subsidies, and corruption in connection with the profitability of investments in wells; and (4) the tying of loans for the cultivation of commercial crops to the arrangements for marketing them. The central importance of villagers' outside options and access to credit emerges clearly
World Bank E-Library Archive
Keywords: 1980-1982